2021
DOI: 10.1039/d0tb02254c
|View full text |Cite
|
Sign up to set email alerts
|

Montmorillonite nanosheets with enhanced photodynamic performance for synergistic bacterial ablation

Abstract: Montmorillonite (MMT), as a naturally sourced and FDA-approved biomaterial, has attracted considerable attention due to its extensive application in biomedical area, such as intestinal aliments, drug delivery, and additive manufacturing....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…Montmorillonite (MMT) is a major ingredient of bentonite and is approved by the Food and Drug Administration of the United States (FDA) for medical use [15,16]. MMT can act as a filler in a polymeric matrix, and this has attracted the attention of scientists especially for the enhancement of the thermal and mechanical properties of native polymers [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Montmorillonite (MMT) is a major ingredient of bentonite and is approved by the Food and Drug Administration of the United States (FDA) for medical use [15,16]. MMT can act as a filler in a polymeric matrix, and this has attracted the attention of scientists especially for the enhancement of the thermal and mechanical properties of native polymers [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…According to the IUPAC classification, MMT and TPCI/MMT presented a type IV adsorption branch with H3-type hysteresis loops, belonging to multimolecular layer adsorption. These characteristics were corresponding to the layered structure of MMT and TPCI/MMT, which were caused by slit shaped pores between parallel layers . The larger specific surface area of TPCI/MMT was conducive to bacteria attraction, which could facilitate the further bacteria elimination. , …”
Section: Results and Discussionmentioning
confidence: 97%
“…Montmorillonite (MMT), a natural aluminomagnesium silicate clay, has attracted considerable attention due to its extensive application in biomedical areas, such as intestinal ailments, drug delivery, and additive manufacturing. , MMT is composed of a three-layered lamellar structure with aluminum oxide octahedra in the middle and silicon oxygen tetrahedra on the top and bottom sides. , The highly ordered lattice arrangement and compact packing of tetrahedron and octahedron structures endow MMT characteristics of high cation exchange capacity and large surface area with excellent adsorption and drug loading properties. , Although some studies have revealed that MMT can adsorb bacteria and bacterial enterotoxins when taken as anti-inflammatory medicine, the antibacterial effect of MMT itself in vitro is actually weak. , …”
Section: Introductionmentioning
confidence: 99%
“…We next characterized CNC–MMT–PEG, in which MMT was utilized to enhance the dispersibility and biocompatibility of CNC. MMT is a highly dispersive 2D layered aluminosilicate filled with various cations, including Fe 3+ (3.31 wt %), in its interlayered space . Possessing a large surface area, layered MMT could easily load 2D CNC to form interesting 2D carbon–2D clay nanohybrids.…”
Section: Resultsmentioning
confidence: 99%